Two-Step Substitution Reaction of Phosphonates Carrying a Binaphthyl Group with Grignard Reagents Leading to the Formation of P-Chirogenic Phosphine Oxides - Ono, Shunya; Sugiyama, Aya; Sakamoto, Nao; Kuwabara, Kazuma; Minoura, Mao; Murai, Toshiaki (Synlett, 2022)
The reaction of phosphonates carrying a binaphthyl group with a range of Grignard reagents was complete within two hours at 0 °C to give phosphinates carrying a hydroxybinaphthyl group with high efficiency and diastereoselectivity. The resulting phosphinates were further subjected to a substitution reaction with MeMgBr. The reaction at reflux temperature in THF or toluene permitted the formation of P-chirogenic tertiary phosphine oxides with a high enantiomeric ratio. Rare examples of P-chirogenic alkynyl phosphine oxides were also obtained. The sequential one-pot substitution reaction of phosphonates bearing a binaphthyl group with two different Grignard reagents successfully gave the corresponding P-chirogenic phosphine oxides with enantiomeric ratios nearly equal to those of oxides derived from two-step reactions.
Keywords: chirogenic compounds; phosphine oxides; binaphthyl phosphonates; chirality transfer reaction; one-pot reaction